Youth's perception towards the credibility of Harian Metro / Nor Raihan Abu Bakar, Norhayati Baba and Sharifah Yuliana Syed Ali Hanafiah - Abu Bakar, Nor Raihan; Baba, Norhayati; Syed Ali Hanafiah, Sharifah Yuliana (2011)
The issue of credibility has been a major challenge for the media. Accuracy and reliability are elements that are highly sought after by the people who are interested in news from the media. Credibility has also become a key factor for a medium to become acceptable to its consumers. The core of credibility is trustfulness, which builds an audience's trust and identification toward a newspaper (Guo et. aI, 2010). Some of the long-standing media credibility combine the concepts of believability, accuracy and depth of information to measure and confer credibility on news items. Hard news which focusing on event oriented, major issues and affects policy are perceived more credible than the soft news (Miller and Kurpius, 2010). As a tabloid style newspaper, Harian Metro devotes much of it stories to soft news, which is described as sensational, and entertainment. This has sparked questions on whether these criteria are considered by the public as credible. Since the newspaper has maintained the overall newspaper readership in Malaysia, it is deemed necessary to find out on whether public has fully trusted the tabloid. An investigation on whether public rationalize the newspaper to pass judgment and decide to accept the content of the news items is crucial in understanding the perceived credibility of the newspaper. In this study, we propose to investigate perceived credibility of young adult readers of Harian Metro in term of news article and news sources. This is carried out by a questionnaires survey that will be distributed to consumers between the ages of 20-40, the stage where every nation believes that they play significant role for its future. This study will be delving at these research questions on understanding the young adult perception on the credibility of Harian Metro.